2018
DOI: 10.1002/advs.201870062
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Protein Sorting: Proteoliposome Engineering with Cell‐Free Membrane Protein Synthesis: Control of Membrane Protein Sorting into Liposomes by Chaperoning Systems (Adv. Sci. 10/2018)

Abstract: Cell‐free membrane protein (MP) synthesis in the presence of liposomes is a spotlighting technique to prepare MP‐reconstituted liposomes. In article number https://doi.org/10.1002/advs.201800524, Kazunari Akiyoshi and co‐workers develop an artificial MP sorting system based on polyhistidine/nickel‐chelate affinity. This system enables efficient reconstitution of MPs into the liposomal membrane to be achieved, and supplementations of natural molecular chaperone can control the orientation of MPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[ 54 ] It has been reported that membrane proteins are incorporated into liposome membranes by PUREsystem expression in the presence of liposomes. [ 27,55 ] In this section, membrane protein expression was performed in the presence of lipid membrane‐coated particles, and the function of the membrane proteins incorporated into the surface of the particles was investigated. The Spike protein (S protein) of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) was selected as the membrane protein in this study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 54 ] It has been reported that membrane proteins are incorporated into liposome membranes by PUREsystem expression in the presence of liposomes. [ 27,55 ] In this section, membrane protein expression was performed in the presence of lipid membrane‐coated particles, and the function of the membrane proteins incorporated into the surface of the particles was investigated. The Spike protein (S protein) of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) was selected as the membrane protein in this study.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this issue, we recently developed a liposomal chaperoning system integrating a polyhistidine/nickel-chelate group pair (Figure 3b). 56 In the presence of nickel-chelating liposomes, N-terminal hexahistidine-fused membrane proteins were synthesized by the cell-free protein synthesis system. Owing to the high affinity between the nickel-chelate group and hexahistidine, the polypeptide of the membrane proteins interacted with the nickel-chelating liposome surface, which enhanced the incorporation of membrane proteins into the lipid membranes.…”
Section: Artificial Chaperone Systems For Proteinmentioning
confidence: 99%
“…Although this system was effective in the incorporation of membrane proteins, its integration efficiency was not sufficient. To overcome this issue, we recently developed a liposomal chaperoning system integrating a polyhistidine/nickel-chelate group pair (Figure b) . In the presence of nickel-chelating liposomes, N -terminal hexahistidine-fused membrane proteins were synthesized by the cell-free protein synthesis system.…”
Section: Artificial Chaperone Systems For Protein Foldingmentioning
confidence: 99%
See 1 more Smart Citation
“…28 This approach has the benet of precise control over antigen presentation but comes with drawbacks including innate immunogenicity of the DNA origami structures. 29 As for liposome-based systems, previous studies have set precedent for the successful incorporation of integral membrane proteins into synthetic membranes, [30][31][32][33][34] including studies in which liposomes have modelled other viruses, such as HIV-1. [35][36][37] For SARS-CoV-2, recently natural and synthetic vesicles have been used to create VLPs by chemically conjugating the receptor-binding-domain (RBD) of the spike glycoprotein to membrane components.…”
Section: Introductionmentioning
confidence: 99%